Analysis of Logical Atomism in Private Expressions “Anjing Menggonggong Kafilah Berlalu” - Rahmawati , Lela; Hilda Hastuti; Aprianto, Dedi; Akbar Adwinata (Jurnal Ilmu Sosial dan Humaniora, 2024)
This study examines the concept of Logical Atomism within the framework of private expressions, with a specific focus on the Indonesian proverb “Anjing Menggonggong, Kafilah Berlalu” (The dogs bark, but the caravan moves on). Logical Atomism, as proposed by Bertrand Russell and further developed by Ludwig Wittgenstein, suggests that complex propositions can be analyzed into simpler, logically independent facts. This paper explores the application of this theory to private and metaphorical expressions, which often convey subjective and context-dependent meanings. This research using descriptive qualitative methods are methods that explain objects, phenomena or social settings that will be outlined in narrative writing. By deconstructing the proverb, the analysis investigates whether its components can be reduced to atomic facts or if the expression's meaning emerges only within a broader cultural or pragmatic context. The study also discusses the tension between the literal interpretation of the statement and its metaphorical implication in expressing resilience or indifference to criticism. Ultimately, the paper highlights the limits of Logical Atomism when applied to private expressions, raising questions about the theory's applicability to subjective and metaphorical language the proverb The Dog Barks the Caravan Passes on explains the importance of analyzing and understanding thoughts logically. Language analysis this proverb can be done by dividing it into atomic propositions or elementary propositions through logical analysis as presented by Russell, namely by breaking it down into atomic parts, namely the Dog Barking and the Caravan Passing. By understanding the atomic part of the proverb, The Dog Barks the Caravan Passes Away, we are able to understand the meaning and message of the proverb by relating it to real life reality. The message of this proverb teaches us to stay focused and remain positive even though there are many negative things around us. This is in accordance with the reality of real human life.